CHARACTERISTICS OF PHYSICAL EDUCATION OF CHILDREN OF KINDERGARTEN AND SCHOOL AGE - Sh. A. Abdujalilova (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the characteristics, forms and means of physical education of preschool and school-aged children.